Integrating and Inter-Connecting the Qur’an-Hadith and Science Education: a Study of Madrasah Aliyah Al-Imdad, Yogyakarta - Marhumah, Ema (International Journal of Engineering and Technology, 2018)
It is interesting to criticize on how is the model and educational application of Qur'an Hadith with science look like. Integrative-interconnected education is an educational model which synchronizes and unites religious education and secular education. The Qur'an-Hadith as one of the disciplines taught in Madrasah has been influenced by the dichotomy dualism of education. The implication is that all things is merely viewed from two opposite angles. The further implications is that the understanding the Qur'an-Hadith tend to narrow an angle of meaning which focus on spiritual life, namely it is considered separated from worldly life. This article examines the process by which learning the Qur’an and Hadith are integrated with natural sciences in Madrasah Aliyah, Islamic Senior High School. I use Madrasah Aliyah Al-Imdad, located in Bantul, Yogyakarta, Indonesia, as a case study. The school is interesting, for it is directed only to deepen Islamic sciences.